Footwall mineralization during Late Miocene extension along the West Cycladic Detachment System, Lavrion, Greece. (1st December 2012) - Berger, Alexandra; Schneider, David A.; Grasemann, Bernhard; Stockli, Daniel
Abstract The West Cycladic Detachment System (WCDS) has been mapped from the western Cycladic islands to Lavrion (mainland Greece), where several top‐to‐SSW low‐angle normal faults at different structural levels are observed. Near the detachment horizon, hydrothermal fluid flow originating from Miocene intrusions lead to high‐temperature carbonate strata‐bound Pb–Ag–Zn ore deposits. Zircon (U–Th)/He cooling ages from the mineralized footwall are 7.1 ± 0.6 to 7.9 ± 0.6 Ma. Carbon‐ and O‐isotope analyses of the carbonate host indicate high water‐to‐rock ratios during brittle deformation‐induced metasomatism, and that this interaction, unrelated to proximity of the intrusions, plays the dominant role in the mineralization. The Late Miocene geology of Lavrion is strikingly similar to Serifos island on the SE termination of the WCDS, both characterized by strong localization of detachment faulting and the interaction of brittle deformation with the injection of fluids related to granitoid intrusions.